2018
DOI: 10.1186/s12891-018-2143-2
|View full text |Cite
|
Sign up to set email alerts
|

A protocol for a multicentre, randomised, double-blind, placebo-controlled trial to compare the effect of annual infusions of zoledronic acid to placebo on knee structural change and knee pain over 24 months in knee osteoarthritis patients – ZAP2

Abstract: BackgroundBisphosphonates are a class of drugs that slow bone loss and are a promising candidate to treat knee osteoarthritis (OA) patients. In a pilot study, we demonstrated that zoledronic acid reduced knee pain and size of subchondral bone marrow lesions (BMLs) over 6 months in knee OA patients with significant knee pain and BMLs. A longer, larger study is required to assess whether decreases in BML size will translate to reductions in cartilage loss over time. We are currently conducting a multicentre, ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 68 publications
0
31
0
1
Order By: Relevance
“…96 Alendronate treatment improved the Western Ontario and McMaster University Osteoarthritis Index pain score, decreased biochemical markers and increased the BMD in a prospective 2-year trial 97 Moreover, compared with those receiving placebo, patients with symptomatic knee OA who received intravenous zoledronic acid yearly did not show a significant reduction in cartilage volume loss, the size of BMOLs or the pain score over 24 months. 98 There are other antiresorptive agents (such as OPG, cathepsin K (CTSK) inhibitors and strontium ranelate) that may exert protective effects on subchondral bone and cartilage in animal models and serve as disease-modifying OA drugs for clinical treatment of OA. [99][100][101] Intriguingly, calcitonin, which is known for targeting subchondral bone remodelling, also leads to intracellular cAMP accumulation and then promotes chondrocyte anabolism by binding to its receptors on human OA chondrocytes.…”
Section: Targeting the Subchondrol Bone Microenvironment For The Treamentioning
confidence: 99%
“…96 Alendronate treatment improved the Western Ontario and McMaster University Osteoarthritis Index pain score, decreased biochemical markers and increased the BMD in a prospective 2-year trial 97 Moreover, compared with those receiving placebo, patients with symptomatic knee OA who received intravenous zoledronic acid yearly did not show a significant reduction in cartilage volume loss, the size of BMOLs or the pain score over 24 months. 98 There are other antiresorptive agents (such as OPG, cathepsin K (CTSK) inhibitors and strontium ranelate) that may exert protective effects on subchondral bone and cartilage in animal models and serve as disease-modifying OA drugs for clinical treatment of OA. [99][100][101] Intriguingly, calcitonin, which is known for targeting subchondral bone remodelling, also leads to intracellular cAMP accumulation and then promotes chondrocyte anabolism by binding to its receptors on human OA chondrocytes.…”
Section: Targeting the Subchondrol Bone Microenvironment For The Treamentioning
confidence: 99%
“…ZOL has the advantages of long-acting, obvious, and fast-acting effect, and significantly improving bone density. A multicenter, randomized, double-blind, controlled trial that administered ZOL and placebo at 6, 12, 18, and 24 months ultimately concluded that ZOL administration reduced bone mass loss and pain [ 18 ]. Cai et al conducted a trial in patients aged >40 years who had low back pain and vertebral modic changes for 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Third, some baseline characteristics were not well balanced, but we have taken this into account by adjusting for them in data analyses according to the trial protocol. 28 Four, the sample size was calculated based on the primary hypothesis. The noninferiority test between ZA and VOLT01 and superiority tests of ZA and VOLT01 with placebo on knee symptoms and BMLs may be underpowered, making the results hypothesis generating.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria were the same as for the ZAP2 trial as previously published. 28 Briefly, we excluded patients with prior use of bisphosphonates except according to a washout schedule, a history of nontraumatic iritis or uveitis, abnormal blood tests (i.e. serum calcium >2.75 mmol/l or <2.00 mmol/l, creatinine clearance <35 ml/min or 25-hydroxyvitamin D concentrations <40 nmol/l), cancer, poor dental health, severe knee osteoarthritis [defined as a joint space narrowing on X-ray of Grade 3 using the Osteoarthritis Research Society International (OARSI) atlas 30 ], knee surgery or arthroscopy in the last 12 month, a corticosteroid injection in the last 3 months, or a hyaluronic acid injection in the last 6 months in the study knee.…”
Section: Methodsmentioning
confidence: 99%